PENGARUH PENGGUNAAN LKS BERBANTUAN MEDIA POWER POINT YANG DILENGKAPI ANIMASI PADA MODEL DIRECT INSTRUCTION TERHADAP PENCAPAIAN KOMPETENSI FISIKA SISWA KELAS X SMAN 5 BUKITTINGGI - Niswatul Khasanah; Yurnetti Yurnetti; Hidayati Hidayati (Universitas Negeri Padang, 2017)
The low competence of students in the physics caused by difficult students in understanding the concepts of physics, materials used have not made use of the media as well as active students have not varied.One of the solutions given Student Work Sheets (LKS) assisted media power point which features animation. The purpose research is to investigate the differences and relationship of the use of assisted LKS media power point which features animated models direct insruction with achievement of competence of students of class X SMAN 5 Bukittinggi. The type of research used in this study was quasi experimental research studies randomized control group only design. The population of the entire research grade X IPA are registered on an even semester academic year 2016/2017 sampling and cluster random sampling technique. Research data includes two competencies, knowledge and competency competency skills as well as values is LKS. Instrument data in the form of a final test for competence of knowledge and competence for performance pieces of skill. Data obtained from the instrument are analyzed in the form of a test of similarity of two average, regression test and correlation value is LKS in class experiments. The results of the analysis show the average value on competence of the knowledge experimental class higher than the class of the control knowledge competencies. Calculation of test equality of two average in competence of the knowledge obtained t'h = 3.10 is greater than t`t = 2.03, so the working hypothesis accepted. Through regression analysis and correlation obtained the relationship between the value of knowledge and competence is LKS as a strong student, with percentage contributions to 74.62% is LKS on the real extent of 0.05 so that research can be concluded there is a difference in meaning is LKS as media-assisted use of power point animation that comes in models for direct instruction against the competence of physics students of class X SMAN 5 Bukittinggi